Pengaruh Kecerdasan Buatan Terhadap Minat Belajar Mahasiswa UIN Imam Bonjol Padang - Fransiska, Resita Eka; Mislaini; Fikri, Ibnu (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2025)
This study aims to explore the impact of artificial intelligence (AI) implementation on students' learning interest at UIN Imam Bonjol Padang and their perceptions of this technology. Using a qualitative case study approach, data were collected through observation and surveys from 25 students and analyzed thematically. The findings reveal that AI enhances students' understanding of learning materials (52%) and engagement in class discussions (68%). However, its influence on learning motivation remains low (36%), and its effectiveness for complex tasks, such as final projects, is limited. Criticism also highlights the potential dependency on AI, which may reduce students' self-evaluation abilities. The study concludes that while AI effectively supports understanding and participation in learning, further development is needed to boost learning motivation and mitigate the risks of technological dependency.